2011
DOI: 10.1103/physreve.84.026330
|View full text |Cite
|
Sign up to set email alerts
|

Drag force on a sphere moving toward an anisotropic superhydrophobic plane

Abstract: We analyze theoretically a high-speed drainage of liquid films squeezed between a hydrophilic sphere and a textured superhydrophobic plane that contains trapped gas bubbles. A superhydrophobic wall is characterized by parameters L (texture characteristic length), b1 and b2 (local slip lengths at solid and gas areas), and φ1 and φ2 (fractions of solid and gas areas). Hydrodynamic properties of the plane are fully expressed in terms of the effective slip-length tensor with eigenvalues that depend on texture para… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 49 publications
4
29
0
Order By: Relevance
“…Since at short separations we observe f * → 0, one can conclude that slippage (which would lead to f * → 1/4 [20]) obviously does not mimic roughness when h is small, by overestimating the drag force. The same remark concerns effective superhydrophobic slippage where f * → 2(4 − 3φ)/(8 + 9φ − 9φ 2 ) [21] and is equal to 0.3 for this particular sample. Therefore, our experimental results are now compared with theoretical calculations made for an effective smooth plane shifted down from the top of the corrugations, i.e., by assuming Table I Table I we present the experimental values of s for different samples, and curves calculated with Eq.…”
Section: Resultsmentioning
confidence: 68%
“…Since at short separations we observe f * → 0, one can conclude that slippage (which would lead to f * → 1/4 [20]) obviously does not mimic roughness when h is small, by overestimating the drag force. The same remark concerns effective superhydrophobic slippage where f * → 2(4 − 3φ)/(8 + 9φ − 9φ 2 ) [21] and is equal to 0.3 for this particular sample. Therefore, our experimental results are now compared with theoretical calculations made for an effective smooth plane shifted down from the top of the corrugations, i.e., by assuming Table I Table I we present the experimental values of s for different samples, and curves calculated with Eq.…”
Section: Resultsmentioning
confidence: 68%
“…In this experiment [31], the authors have assumed that the boundary slip is described by the Vinogradova equation shown above. More recently, Asmolov et al [34] showed that on textured superhydrophobic surfaces, the effective slip length is not independent of the distance in the drainage experiments. Asmolov et al [34] suggested a new expression to evaluate the slip length on textured superhydrophobic surfaces, and it will be useful to check such expressions in forthcoming AFM experiments.…”
Section: (D) Surface Force Apparatus Experimentsmentioning
confidence: 99%
“…1). As in most previous publications [7,12,15,20,29,[35][36][37], we model the superhydrophobic plate as a flat heterogeneous interface. In such a description, we neglect an additional mechanism for a dissipation connected with the meniscus curvature [15,38,39].…”
Section: Model and Governing Equationsmentioning
confidence: 99%